Avaliac ío da popula í§ ío de protozoários ciliados no rúmen, retículo e omaso e do trato digestivo em búfalos alimentados em três níveis de energia - Franzolinl, Raul; Tieghi Franzolin, Maria Helena; da Silva, Juliano Roberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
Three groups of six buffalo males each were fed on three energy levels: LE (Low Energy), RE (Required Energy) and HE (High Energy) in feedlot for around 140 days. RE was calculated with 125 Kcal ME/ kg 0.75 to maintenance; LE with 20% below and HE with 20% above, estimating a gain weight of 800 g/d. Gi-ass hay was used as roughage; the concentrate was a mixture of grain corn ground and soybean meal and composed 39.8% (LE), 48,5% (RE) and 58,1% (AE). Average slaughter body weight was 449 kg and samples of contents from rumen, reticulum and omasum were collected to protozoology study. Daily average dry matter intake was 92.1 g/kg 0.5 and estimated energy intake (Kcal/kg 0.75) were 201,23 (LE), 223,32 (RE) and 241,20 (HE). There was difference (P